Biomimetic Growth of Metal–Organic Frameworks for the Stabilization of the Dentin Matrix and Control of Collagenolysis - Bim-Junior, Odair [UNESP]; Alania, Yvette; Tabatabaei, Fahimeh Sadat; Frem, Regina [UNESP]; Bedran-Russo, Ana K.; Lisboa-Filho, Paulo N. [UNESP] (American Chemical Society (ACS), 2022)
The dentin matrix is a collagenous scaffold structurally involved in anchoring resin-based materials to the tooth. Time-dependent degradation of this scaffold at the resin–dentin interface remains a core problem in adhesive dentistry, limiting the service life of dental fillings. This study explored the use of emergent materials termed metal–organic frameworks (MOFs)─formed by the self-assembly of metal ions and organic building blocks─to safeguard the collagen integrity in the functional dentin matrix. We demonstrate that collagen fibrils (from demineralized human dentin) can induce the biomimetic growth of MOF crystals as protective coatings to strengthen and stabilize the fibrils. Zeolitic imidazolate framework-8 (ZIF-8), a zinc-based microporous MOF, was used to fabricate the MOF composites via a “one-pot” reaction in water. The ZIF-modified dentin matrix presented superior mechanical strength and resistance to proteolysis, which can positively affect the longevity of collagen as an anchoring substrate. This work identifies a potential biomedical application of biomimetically synthesized MOFs in repairing dental tissues critical to restorative therapies.